INVESTIGATION OF DESIGN AND PERFORMANCE CHARACTERISTICS OF MATERIALS USED IN CEMENT MORTAR MIXTURES DESIGNED FOR SEMI-RIGID PAVEMENTS - El, Alev Akıllı; Yalçın, Erkut; Yılmaz, Mehmet (My University, 2025)
Semi-rigid pavements are a type of pavement constructed by injecting a flowable cement mortar into the voids of a compacted porous asphalt skeleton with a void percentage between 25-35%. Cement mortar is one of the most important components for semi-rigid pavements, but the properties of the mortar are not well researched. The design of cement mortar for semi-rigid pavements is different from the traditional cement mortar used for concrete design. In semi-rigid pavements, workability, flowability and strength of mortars play an important role in the performance level of mixtures. In this study, the properties, mixing ratios and performance characteristics of the materials in cement mortar used in the production of semi-rigid pavement systems were evaluated. In the study, the flowability and compressive strength properties of cement mortar prepared using two different aggregates, different w/c ratios and different proportions of superplasticizing admixtures were investigated. In addition, research on the materials, design and performance of cement mortar is summarized and presented. As a result of this study, it was determined that in order for the cement mortar to penetrate well into the voids in porous asphalt, the w/c ratio used should be kept low and the ratio of superplasticizing additive should be maximum 2%.
Keywords: Cement Mortar; Design; Material; Semi Rigid Pavement